ANÁLISE DA GENOTOXICIDADE ERITROCITÁRIA E HISTOPATOLOGIA BRANQUIAL EM LAMBARIS (Astyanax lacustris) EXPOSTOS AO INSETICIDA LAMBDA-CIALOTRINA - LIDIANE CECILIA PEREIRA (2024)
Brazil is a major global agricultural producer and consumer of pesticides. The use of pesticides has significantly increased from 2010 to 2020, outpacing the growth in cul-tivated areas. Despite regulations, managing these chemicals still presents challeng-es. The Brazilian Health Regulatory Agency (Anvisa) has banned certain pesticides, potentially increasing the use of pyrethroids, which are considered safe due to their selective toxicity but can contaminate aquatic environments. Lambda-cyhalothrin (LC) is a pyrethroid insecticide widely used in agricultural and domestic pests. While it is less toxic to birds and mammals, its introduction into aquatic ecosystems can harm non-target organisms. It can occur mainly through drift during spraying, leaching, sur-face runoff, and even direct application to water bodies. The primary aim of this study was to assess the sublethal effects of exposure to the pyrethroid insecticide lambda-cyhalothrin on Astyanax lacustris, using genotoxic and histopathological markers. Eighty juvenile specimens of A. lacustris were divided into eight experimental groups, with four groups exposed to a concentration of 1.5 μg/L of LC for 1, 3, 6, and 12 days, respectively. Ten specimens were used for each period. The study evaluated the genotoxic effects by analyzing the frequency of nuclear alterations and micronuclei in erythrocytes, as well as quantifying histopathological alterations in gill tissue. The results indicate an increase in nuclear abnormalities, specifically binucleated and invaginated nuclei, in fish exposed for 1, 3, and 6 days compared to those not ex-posed. Histological lesions were observed, including desquamation of the epithelium, edema in the secondary lamellae, lamellar adhesion, hyperplasia, hypertrophy of the mucus cells, aneurysms, and complete fusion of the secondary lamellae in more se-vere cases (12 days). The results suggest that the sublethal concentration of LC is toxic to A. lacustris from three days onwards. The results indicate the necessity of agricultural biomonitoring and risk assessment when using insecticides, mainly due to the negative impact on non-target aquatic species. Additionally, A. lacustris may be included in the list of bioindicator species for future ecotoxicological impacts of pyre-throid insecticides. This highlights the need for new conservation and environmental management strategies to reduce contaminant exposure and preserve regional biodi-versity. Keywords: Genotoxicity. Histopathology. Pyrethroid. Fish.